A Study of Thai vocal techniques in Sud sa-nguan Sam chan: A case study of Khru Chareonjai Suntharawathhin’s singing from the album ‘Benjaphan’ released on the Kamonsukosol label - Thongphool, Sasiwong; Kanchanapradit, Jarun; Seemuang, Jatuporn (Journal of Music and Performing Arts Khon Kaen University, 2025)
The objectives of this research are as follows: (1) to examine the personal style of Ajarn Chareonjai Suntharawathhin 's singing techniques in the ‘Benjaphan’ released on the Kamonsukosol label recording Sud-sa-nguan Sam chan; and (2) to analyze the pattern of melodic arrangement, grouping of song texts, and breathing position of Ajarn Chareonjai Suntharawathhin's techniques. The research was conducted according to a qualitative research approach, including documentary research and interviewing experts in classical Thai music singing, analyzing the main melody, and analyzing the particular techniques of singing. The results found that there are two methods to the Ajarn Chareonjai Suntharawathhin singing technique: the strategy of Oyen (เอื้อน) and Pan-Khaam (ปั้นคำ), the strategy of creating a sound for lyrics. The techniques of Oyen include Oyen-Sam-Siang (เอื้อนสามเสียง), Oyen-Kratop-Siang (เอื้อนกระทบเสียง), Phan-Siang (ผันเสียง), and Khran (ครั่น). Of these, four are made up of 13 sub-units of Oyen. In the Pan-Khaam strategy, there are two types of expressive word formation to convey meaning and emotion: one word and one sound, and one word—many sounds. There are two types of word groupings: three-part word groups, such as 3-2-3, and four-part word groups, such as 2-1-2-3. Most melodic arrangements fall between bars 1–6 of each line. Bars 7-8 are the locations of the song lyrics. Most breathing positions occur between the end of the Oyen and before the song lyrics.